2003
DOI: 10.1046/j.1095-8649.2003.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in tolerance to hypoxia in a predator and prey species: an ecological advantage of being small?

Abstract: Three physiological variables, haematocrit, haemoglobin concentration and ventilation frequency, were measured to test how fathead minnows Pimephales promelas and small and large yellow perch Perca flavescens responded to three different dissolved oxygen concentrations. All fish were monitored continuously for any indications of stress in response to these manipulations. Within and between species, smaller individuals were the most tolerant of hypoxic environments. A species effect, however, did contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 59 publications
2
83
1
Order By: Relevance
“…Some larger-bodied fishes are better able to survive severe hypoxia stress due to increased levels of glycogen available for anaerobic adenosine-triphosphate production (Nilsson and Ostlund-Nilsson, 2008). In contrast, Robb and Abrahams (Robb and Abrahams, 2003) found that large yellow perch (~34g) were significantly less tolerant to extreme hypoxia stress than small individuals of the same species (~2g). However, these contrasting reports were based on adult fish, and such assumptions should not be automatically interpolated to the very different situation for developing fish (Burggren, 2005).…”
Section: Larval Body Lengthmentioning
confidence: 92%
See 1 more Smart Citation
“…Some larger-bodied fishes are better able to survive severe hypoxia stress due to increased levels of glycogen available for anaerobic adenosine-triphosphate production (Nilsson and Ostlund-Nilsson, 2008). In contrast, Robb and Abrahams (Robb and Abrahams, 2003) found that large yellow perch (~34g) were significantly less tolerant to extreme hypoxia stress than small individuals of the same species (~2g). However, these contrasting reports were based on adult fish, and such assumptions should not be automatically interpolated to the very different situation for developing fish (Burggren, 2005).…”
Section: Larval Body Lengthmentioning
confidence: 92%
“…The majority of differences between the two groups were observed at 15 and 18d.p.f., with HP-1 diverging from the normal developmental trajectory as early as 6d.p.f. Although the relationship between body size and hypoxia resistance is controversial, the effect of body size has clear implications in the regulation of oxygen consumption (see Feder, 1983b;Feder, 1983a;Burleson et al, 2001;Robb and Abrahams, 2003;Ospina and Mora, 2004;Nilsson and OstlundNilsson, 2008). Some larger-bodied fishes are better able to survive severe hypoxia stress due to increased levels of glycogen available for anaerobic adenosine-triphosphate production (Nilsson and Ostlund-Nilsson, 2008).…”
Section: Larval Body Lengthmentioning
confidence: 99%
“…(2) 87 The 'physiological hypothesis' assumes that natal departure is driven by physiological 88 tolerance to environmental conditions (e.g., Chapman et al 2002). Because of negative 89 allometric relationship for mass-specific gill surface area, small-bodied fish have more 90 efficient oxygen exchange with water compared with large ones and, consequently, they are 91 less sensitive to hypoxia (Hugues 1984;Robb and Abrahams 2003). Therefore, it is expected 92 that body-size at departure decreases when environmental conditions deteriorate (Fig.…”
Section: Schwartz and Jenkins 2000; Jopp Et Al 2010) 52mentioning
confidence: 99%
“…There are indeed indications of an association between a small brain size and a low predation pressure in fishes [71,72], and a growing body of evidence that hypoxic habitats may serve as a refuge for small fishes from large aquatic predators [73][74][75][76]. For example, in the Lake Victoria basin, swamps serve as both structural and low-oxygen refugia for hypoxia-tolerant fishes from the introduced aquatic predator, the Nile perch (Lates niloticus), a species intolerant of hypoxia [32,43,44,76,77].…”
Section: Canalization Of Brain Size In the Swampmentioning
confidence: 99%